The Effect of Driver Performance on Income with Age as a Moderating Variable: Case Study of the Sukabumi Grab Bike Solidarity Community (SOGRABIS) - Rusmayadi, Oki; Maharani, Anita; Nur Fitroh, Muhammad; Mawarni, Gesi (International Journal of Business, Law, and Education, 2024)
This study explores the relationship between performance and income in the field of app-based drivers, with a specific focus on the moderating role of age. Involving 100 respondents from the SOGRABIS population in Sukabumi, this research employs Moderated Regression Analysis (MRA) to analyze the impact of performance on income and how age moderates this relationship. The findings indicate that performance significantly and positively influences the income of drivers, and age plays a role in moderating this relationship by weakening the impact of performance on income. These results provide valuable insights for platform managers and field workers in enhancing working conditions and driver income.